Pemeliharaan Dan Penyimpanan Peralatan Laboratorium Kimia - J Jufriyah; Isna Mar'ah; Kelik Isharyudono (Jurnal Pengelolaan Laboratorium Pendidikan, 2019)
Improper maintenance and storage of laboratory equipment, will shorten the life span. Damage to the tool will have a direct impact on the costs that must be incurred to replace damaged equipment components or even procurement of new equipment. The purpose of this paper is to provide an understanding of how to maintain and store chemical laboratory equipment. And can identify damage to chemical laboratory equipment. Broadly speaking, the tool maintenance method is divided into two parts: planned maintenance and unplanned maintenance. For storage of tools using the classification method based on the tool group, frequency of use and the nature of the tool. Maintenance and storage of chemical laboratory equipment is an activity process in order to anticipate damage as early as possible so that it can increase the efficiency of the working life of the equipment used. So that the chemical laboratory equipment can function optimally and always in a state of ready use, it is necessary to have knowledge about how to maintain and store laboratory equipment and how to identify equipment damage as early as possible. Maintenance and storage of chemical laboratory equipment properly can prevent damage to chemical laboratory equipment that will extend the life of the equipment, and ensure the comfort and safety of the user.